Tinjauan Hukum Islam terhadap Pinjaman Kredit Usaha Masyarakat di Unit BUMDes “Loh Jinawi” Desa Candipari Kecamatan Porong Kabupaten Sidoarjo - Faruq, Muhammad Al; Masduqie, Muhammad Hamdan Ali; Djalaluddin, Ahmad Ahmad (TAWAZUN: Journal of Sharia Economic Law, 2023)
Mu'amalah in the Islamic context requires fellow human beings to cooperate and relate to each other to increase benefit and not cause harm to each other. The debt receivables agreement is intended to help each other among fellow human beings, tosolvean problem and facilitate the continuity of hislife. The purpose of this study is to analyze the borrowing of community business loans in the BUMDes unit "Loh Jinawi" Candipari Village, Porong District, Sidoarjo Regency based on a review of Islamic law. This research is a field research (field research). The research used is qualitative research, where the author conducts research by looking for direct data in the field to understand comprehensively how the implementation of business credit loans in the community in the BUMDes unit "Loh Jinawi" Candipari Village, Porong District, Sidoarjo District viewed from Islamic law. The results of the research obtained by the researchers showed that the practice or mechanism of community business credit loans in the BUMDes unit "Loh Jinawi" candipari village, Porong district, Sidoarjo Regency, found that there was interest interest charged to borrowers or debtors. So according to the clerics' adherents of madzhab imams, if in a contract of debts there is an additional element or interest then the law is illegitimate.